Contribution of the infection ecosystem and biogeography to antibiotic failure in vivo - Rahan Rudland Nazeer; Isabel Askenasy; Jemima E. V. Swain; Martin Welch (npj Antimicrobials and Resistance)
Abstract The acquisition of antibiotic resistance in bacteria, though a deeply concerning international issue, is reasonably well-understood at a mechanistic level. Less well-understood is why bacteria that are sensitive in vitro to well-established and widely-used antibiotics sometimes fail to respond to these agents in vivo. This is a particularly common problem in chronic, polymicrobial infection scenarios. Here, we discuss this in vitro-in vivo disconnect from the perspective of the bacterium, focusing in particular on how infection micro/macro-environment, biogeography, and the presence of co-habiting species affect the response to antibiotics. Using selected exemplars, we also consider interventions that might improve treatment outcomes, as well as ecologically ‘eubiotic’ approaches that have less of an impact on the patient’s commensal microflora. In our view, the accrued data strongly suggest that we need a more comprehensive understanding of the in situ microbiology at infection sites.